(untitled) (The Review of Diabetic Studies, 2025)
This descriptive analytical study aims to explore the future qualification level of paramedics in health education programs offered at Saudi universities, in light of the increasing expansion of emergency services and the continuous need for paramedics capable of responding effectively to critical cases. The study begins with an analysis of the nature of the current curricula and the extent to which they include the basic and advanced skills needed by paramedics, such as advanced cardiopulmonary resuscitation skills, managing multiple injuries, and working within multidisciplinary medical teams. The study also seeks to determine the extent to which these educational programs are compatible with the future requirements of the labor market and the standards of international bodies concerned with the qualification of paramedics. The study is based on an evaluation of the quality of practical and clinical training students receive during their university studies and the effectiveness of existing partnerships between universities and healthcare institutions in enhancing their practical skills. Finally, the study addresses the challenges facing health education programs, such as limited training resources, a shortage of field facilities, and insufficient training in high-fidelity simulation environments. The study as a whole seeks to identify the gap between the theoretical and practical skills that the student receives during the education stage, and what he actually needs when he joins the field work within ambulance and emergency systems. The results are expected to contribute to developing recommendations that support improving the efficiency of educational programs, developing curricula, and strengthening field partnerships, in order to ensure that paramedics are more prepared and responsive to the requirements of the future in the Kingdom of Saudi Arabia.